Indonesian Pre-Service English Teachers’ Experiences and Perspectives on Participating in a Student Exchange Program: A Qualitative Study - Markus Deli Girik Allo; Roni La’biran; Adaninggar Septi SubektI; Lemmuela Alvita Kurniawati; Sushy Teko Patanduk; Judith Ratu Tandiarrang (STAI Hubbulwathan Duri, 2025)
Student exchange programs such as Merdeka Belajar Kampus Merdeka (MBKM) offer valuable opportunities for pre-service teachers to gain teaching experience, enhance language skills, and develop intercultural competence. However, limited research has explored participants’ lived experiences and perspectives within these programs. This qualitative study investigated the experiences and perspectives of five Indonesian pre-service English teachers who participated in the MBKM student exchange program for one semester. Data were collected through semi-structured interviews and a focus group discussion, then analyzed using thematic analysis to identify key themes. The findings revealed that participants experienced notable professional and personal growth. Key experiences included virtual teaching, classroom observations of diverse pedagogical methods, improved English language proficiency, and enhanced cultural adaptability. Participants also articulated their perspectives on the student exchange program across three main dimensions: the program’s definition, its academic and cultural scope, and its perceived significance. They recognized the program as a platform for cross-cultural engagement and professional development. The MBKM student exchange program positively impacted the participants by broadening their pedagogical insight, fostering language development, and strengthening their readiness to teach in diverse contexts. These findings suggest that such programs are instrumental in preparing globally competent educators. This study underscores the value of student exchange initiatives in teacher education. Institutions and policymakers are encouraged to sustain and expand such programs to maximize their benefits for future educators.